2001
DOI: 10.2307/3515602
|View full text |Cite
|
Sign up to set email alerts
|

Middle Jurassic (Bajocian and Bathonian) Dinosaur Megatracksites, Bighorn Basin, Wyoming, U.S.A.

Abstract: Two previously unknown rare Middle Jurassic dinosaur megatracksites are reported from the Bighorn Basin of northern Wyoming in the Western Interior of the United States. These trace fossils occur in carbonate units once thought to be totally marine in origin, and constitute the two most extensive Middle Jurassic dinosaur tracksites currently known in North America. The youngest of these occurs primarily along a single horizon at or near the top of the ''basal member'' of the ''lower'' Sundance Formation, is mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 12 publications
0
61
0
Order By: Relevance
“…This set of beds represents the last transgressive-regressive cycle of the Sundance Seaway (Brenner and Peterson, 1994). Molluscan biostratigraphy places this member in the Oxfordian (Kvale et al, 2001). It is highly fossiliferous, with numerous invertebrate remains and occasional, usually isolated, vertebrate remains.…”
Section: Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…This set of beds represents the last transgressive-regressive cycle of the Sundance Seaway (Brenner and Peterson, 1994). Molluscan biostratigraphy places this member in the Oxfordian (Kvale et al, 2001). It is highly fossiliferous, with numerous invertebrate remains and occasional, usually isolated, vertebrate remains.…”
Section: Geological Settingmentioning
confidence: 99%
“…The Sundance Seaway was a shallow epicontinental seaway that covered much of Wyoming and parts of Montana, South Dakota, and Colorado in the late Jurassic (Kvale et al, 2001). Marine sediments deposited by this seaway in southeastern Wyoming were named the "Shirley Stage" by Knight (1900), and later the Sundance Formation by Reeside (1919).…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is stratigraphically slightly higher than the Howe Quarry, but like all the excavation sites on Howe Ranch, it is located beneath the so-called clay change (see Schwarz et al, 2007a, figure 3), which was used for long-distance correlation by Turner and Peterson (1999) and Ikejiri (2004Ikejiri ( , 2005. The site was dated to 147 Ma by Kvale et al (2001, figure 5), based on its position somewhat above a bentonite layer dated to 151.5 +/-4.0 Ma (Kvale et al, 2001, table 1). FIGURE 1.…”
Section: Stratigraphy and Agementioning
confidence: 99%
“…During the past decade, numerous studies have suggested that the preservation of dinosaur tracks may be, in part, controlled by relative sea level rise (e.g. Lockley et al, 1992Lockley et al, , 2006Lockley and Hunt, 1995;Matsukawa et al, 1999;Kurtz et al, 2001;Kvale et al, 2001). Lockley and Hunt (1995) noted similarities in stratigraphic positioning of track beds/intervals (megatracksites) within the Upper Triassic Chinle Group (Utah, New Mexico, Texas, Oklahoma, Colorado, Arizona, and Wyoming) and the Lower Cretaceous Dakota Group (Colorado and New Mexico).…”
Section: Introductionmentioning
confidence: 99%